An Instant Online CV Creation Workshop Using Generative AI and a Web-Based Platform to Improve Digital Literacy and Job Readiness for Vocational High School Students - Angga Lisdiyanto; Addien Haniefardy; Laqma Dica Fitrani; Agus Wibowo; Ikhwan Abdillah; Nurul Fuad; Winarti; Yerezqy Bagus; Dina Zatusiva Haq; Yoga Ari Tofan; Vinza Hedi Satria (Jurnal Pengabdian Sains dan Humaniora, 2026)
Graduates of Vocational High Schools (SMK) consistently contribute the most to Indonesia's Open Unemployment Rate (TPT), reaching 8.63% as of August 2025. A major issue is students' limited ability to develop relevant digital personal branding aligned with modern recruitment standards, such as having an attractive and accessible online Curriculum Vitae (CV). This community service project (PkM) aims to equip 12th-grade students at SMK Al-Amin Mojowuku, Kedamean, Gresik, with skills to create instant website-based CVs using three free tools: generative AI (DeepSeek), image hosting service (ImgBB), and HTML publishing platform (Tiiny.host). Conducted offline on April 28, 2026, with 28 participants, the workshop employed project-based learning combined with AI-assisted learning. The activity involved needs analysis, module development, workshops through lectures and practical exercises, and output evaluation. Results showed all participants successfully published personal CV websites with various themes such as manga comics, anime, and floral motifs. Quantitative indicators included a 100% task completion rate, high active engagement, and positive feedback on material relevance. This activity effectively improved digital literacy, creativity and prepared students for digital-focused recruitment processes